Metabolic Engineering of Bacterial Respiration: High vs. Low P/O and the Case of Zymomonas mobilis - Kalnenieks, Uldis; Balodite, Elina; Rutkis, Reinis (Frontiers in Bioengineering and Biotechnology, 2019)
Respiratory chain plays a pivotal role in the energy and redox balance of aerobic bacteria. By engineering respiration, it is possible to alter the efficiency of energy generation and intracellular redox state, and thus affect the key bioprocess parameters: cell yield, productivity and stress resistance. Here we summarise the current metabolic engineering and synthetic biology approaches to bacterial respiratory metabolism, with a special focus on the respiratory chain of the ethanologenic bacterium Zymomonas mobilis. Electron transport in Z. mobilis can serve as a model system of bacterial respiration with low oxidative phosphorylation efficiency. Its application for redox balancing and relevance for improvement of stress tolerance is analyzed.